Human Security and Sustainable Development: The Role of Social Studies Education in Nigeria - Habeeb, Aishatu Zubairu (NIU Journal of Social Sciences, 2026)
This study examines the role of Social Studies education in addressing human security challenges and achieving sustainable development in Nigeria. Despite various policy efforts by successive government and leaders, Nigeria continues to face widespread issues such as poverty, insecurity, environmental degradation, and civic apathy, all of which have threaten national development and social stability. These persistent problems highlight the inadequacy of current educational approaches in equipping citizens with the knowledge, values, and skills necessary to respond appropriately to complex societal challenges. Employing a qualitative research methodology, the study analyzes data from scholarly literature, curriculum documents, and policy reports. The theoretical framework combines Human Security Theory and Constructivist Learning Theory, providing insights into how education can empower individuals to contribute meaningfully to peace, security, and development. Findings reveal that Social Studies, when effectively delivered, can foster civic responsibility, critical thinking, environmental awareness, and tolerance which are core components of human security and sustainability. However, the study identifies gaps such as outdated curricula, lack of teacher training, and insufficient linkage between classroom content and real-world challenges. It recommends a reorientation of Social Studies curricula to directly address human security and sustainability themes, professional development for educators, and the integration of participatory, inquiry-based teaching methods. Additionally, policy support is needed to strengthen civic education as a pillar of national development. In conclusion, Social Studies education holds significant potential to shape responsible, informed citizens capable of advancing human security and sustainable development in Nigeria, but this potential can only be realized through strategic reforms in content, pedagogy, and educational policy. Keywords: Human Security, Sustainable Development, Social Sustainability, Environmental Sustainability, Pedagogy, Policy, Social Studies Education.